2005
DOI: 10.1590/s1516-89132005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between continuous and batch processing to produce clavulanic acid by Streptomyces clavuligerus

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There is a growing body of literature related to the comparison between airlift and conventional bioreactors for different applications [12][13][14][15][16][17]. Regarding clavulanic acid production, various studies can be found in the literature related to the improvements in the composition of culture media [6,8,[18][19][20], bioreactor operation mode [3,5,7,[21][22][23] and the influence of oxygen supply and agitation condition on CA production by S. clavuligerus in conventional bench scale bioreactor [4]. However, to the best of our knowledge no articles which compare the performances of conventional and non-conventional pneumatic bioreactors on CA production can be found.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature related to the comparison between airlift and conventional bioreactors for different applications [12][13][14][15][16][17]. Regarding clavulanic acid production, various studies can be found in the literature related to the improvements in the composition of culture media [6,8,[18][19][20], bioreactor operation mode [3,5,7,[21][22][23] and the influence of oxygen supply and agitation condition on CA production by S. clavuligerus in conventional bench scale bioreactor [4]. However, to the best of our knowledge no articles which compare the performances of conventional and non-conventional pneumatic bioreactors on CA production can be found.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of this method is the high recovery yield by this process. Also, as reported by Baptista Neto et al [6] in a study of clavulanic acid production, microfiltration can be used to separate the microorganism in continuous cultures with cell recycling.…”
Section: Introductionmentioning
confidence: 89%
“…Carbono Glicerol (aceite de palma y oliva), glucosa, almidón. [4,[8][9][10][11][12] Nitrógeno Ornitina, prolina, ácido glutámico, proteína aislada de soya, harina de soya, peptona, sulfato de amonio, glutamato monosódico, asparagina. [8,11,13] Oxígeno Oxígeno.…”
Section: Fuente Nutrientes Referenciasunclassified
“…[4,[8][9][10][11][12] Nitrógeno Ornitina, prolina, ácido glutámico, proteína aislada de soya, harina de soya, peptona, sulfato de amonio, glutamato monosódico, asparagina. [8,11,13] Oxígeno Oxígeno. [5,7,13] Elementos traza Cloruro de sodio, sulfato de magnesio, sulfato de manganeso, cloruro de manganeso, carbonato de calcio, sulfato de cobre, cloruro de zinc.…”
Section: Fuente Nutrientes Referenciasunclassified
See 1 more Smart Citation